Similar glacial and Holocene deep water circulation inferred from southeast Pacific benthic foraminiferal carbon isotope composition - Matsumoto, K.; Lynch-Stieglitz, J. (Paleoceanography, 1999)
We present Holocene and last glacial maximum (LGM) oxygen and carbon isotope measurements on Planulina wuellerstorfi in six southeast Pacific cores. Sedimentation rates are low in this part of the ocean, acid measurements were made on individual foraminiferal shells in order to identify the Holocene and glacial individuals on the basis of their extreme delta(18)O. The new delta(13)C data were combined with previous P. wuellerstorfi data for interpretation of global thermohaline circulation. Data from the Southern Ocean were examined closely for regional coherency and a few anomalous delta(13)C values suspected of having productivity overprint were removed. The resulting global delta(13)C distributions and gradients indicate that the deep water circulation was similar during the Holocene and LGM. This interpretation brings delta(13)C data to a better agreement with Cd/Ca data and marks a sharp contrast with a widely held view based on delta(13)C measurements that the glacial Southern Ocean was the terminus of the thermohaline circulation. The proposed presence of glacial North Atlantic Deep Water does not necessarily contradict the postulated presence of Glacial North Atlantic Intermediate Water.
179kdTimes Cited:61Cited References Count:90